2016
DOI: 10.1589/jpts.28.2611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orofacial myofunctional exercise on the improvement of dysphagia patients’ orofacial muscle strength and diadochokinetic rate

Abstract: [Purpose] Measurement of the diadochokinetic rate can provide useful information on swallowing rehabilitation in the oral phase by elucidating the speed and regularity of movement of muscles related to the lips, tongue, and chin. This study investigated the effect of a three-week period of orofacial myofunctional exercise on the improvement of cheek, tongue, and lip muscle strength and diadochokinetic rate in dysphagia patients. [Subjects and Methods] This study employed a pretest-posttest control group design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
0
15
0
8
Order By: Relevance
“…For example, Clark and Solomon [4] measured lip compression strength in 68 young (25 men and 43 women), 41 middle-aged (28 men and 13 women) and 38 older adults (26 men and 12 women), and found the wide ranges of variation in lip strength in all age groups (range between 12 and 73 kPa in young adults, between 13 and 74 kPa in middle-age adults and between 15 and 62 kPa in older adults). Other studies also reported a similar phenomenon [5,11,12]. In healthy individuals, it is unclear whether the difference in lip compression strength affects various functions such as mastication, swallowing, and speech.…”
Section: Discussionmentioning
confidence: 69%
“…For example, Clark and Solomon [4] measured lip compression strength in 68 young (25 men and 43 women), 41 middle-aged (28 men and 13 women) and 38 older adults (26 men and 12 women), and found the wide ranges of variation in lip strength in all age groups (range between 12 and 73 kPa in young adults, between 13 and 74 kPa in middle-age adults and between 15 and 62 kPa in older adults). Other studies also reported a similar phenomenon [5,11,12]. In healthy individuals, it is unclear whether the difference in lip compression strength affects various functions such as mastication, swallowing, and speech.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, when using electrical stimulation to the lip muscles (30 min/day, 5 days/week for 4 weeks), patients with dysphagia after stroke had an improvement in lip muscle strength measured by the IOPI (5.9 to 20.5 kPa) [27]. The change in lip muscle training in patients with stroke resulted in increased lip strength and function [11,13,16,27].…”
Section: Lip Training Responses In Patients With Strokementioning
confidence: 99%
“…Thus, unlike the Lip trainers, this device can prescribe a set intensity for lip strength training. This instrument has been used in research for lip strengthening protocols and evaluations [13,16]. The IOPI measures force using a tongue bulb.…”
Section: Devices Used In Lip Exercise Interventionmentioning
confidence: 99%
See 2 more Smart Citations